Determination of the Heterogeneous Rate Constant of Fe(CN)63-/4- in Aqueous Solutions with Different Supporting Electrolyte and Viscosity at Glassy Carbon Electrode - ALI ROSTAMI, ABBAS; REZANEJAD GATABI, ZAHRA (Asian Journal of Chemistry, 2010)
The apparent standard rate constant, k0, for a Fe(CN)6 3-/4- electrode process, known to be strongly dependent on the nature of supporting electrolyte, display a lateral dependence on the solution viscosity (water/ glucose mixture, 1 M in KCl, NaCl and CsCl). k0, is inversely proportional to the solution viscosity. The viscosity performance is complementary to the catalytic effect of cations and seems to operate independently. The catalytic role of cations is discussed in term of the pre-equilibrium concept, considering the influence of a double-layer potential on the effective concentration of reactant ions at the active site near the electrode.